The Influence of Risk Propensity and Psychological Factors on Investment Decisions - Sitaula, Prakash; Uprety, Pravat (Journal of Business and Social Sciences Research, 2024)
This study focuses on risk propensity and psychological factors influencing investment decisions among individuals in the Nepal Stock Exchange (NEPSE) in Kathmandu, Nepal. It focuses on risk perception, risk tolerance, overconfidence, and loss aversion, drawing on prospect theory and cognitive bias. Utilizing an explanatory research design, data was collected from 278 respondents through structured questionnaires. A quantitative analysis was conducted using both descriptive and inferential statistics, with the PLS-SEM method employed to derive the results. Both risk propensity and psychological factors significantly affect all investment-related decisions, with overconfidence being the most influential. However, it is important to note that the study is limited to investors in Kathmandu who are trading on NEPSE, and the cross-sectional nature of the data may restrict how applicable these findings are to other settings. The study emphasises the need for stakeholders in Nepal’s financial sector to consider these factors when forming financial regulations and investor protection initiatives.